Psychiatry and the Necker Cube. Neurological and Psychological Conceptions of Psychiatric Disorder - D. Rogers (Behavioural Neurology)
Neurological and psychological conceptions of psychiatric disorder are in conflict at the present time. This conflict is considered in the context of the history of psychiatry and the philosophy of science. Its practical consequences are considered for the motor disorder of schizophrenia, the cognitive impairment in psychiatric illnesses, the use of the terms organic and functional and the association of neurological disorder with psychotic and neurotic disorders. The conflict is also examined in individual cases and the implications for treatment assessed.